Researching religious education: classroom processes and outcomes - Schweitzer, Friedrich; Boschki, Reinhold (Glaube, Wertebildung, Interreligiosität, 2018)
The question of how research on structures and outcomes in Religious Education can be carried out successfully is of current interest in many countries. Next to the more traditional historical, analytical and, more recently, international comparative approaches, empirical research in religious education has been able to establish itself as a major approach to this field. Moreover, the contemporary discussion about comparative evaluation in schools has raised a number of questions which also refer to Religious Education. What competences can pupils acquire in this subject? Does Religious Education really support the acquisition and development of the competences aspired? Are there differences in this respect between different forms of Religious Education or between different approaches to teaching? With contributions from eight European countries, the volume brings together approaches and research experiences that try to follow this lead by offering new and empirically based perspectives for the future improvement of teaching and learning in this school subject. Whoever is interested in improving the practice of Religious Education then, will not be able to bypass the question of researching processes and outcomes – an insight which also refers to a small but growing number of studies in this field which can be identified in several countries.